2017
DOI: 10.3847/1538-4357/aa90b8
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Variability of Two Rapidly Rotating Brown Dwarfs: 2MASS J08354256-0819237 and 2MASS J18212815+1414010

Abstract: L dwarfs exhibit low-level, rotationally-modulated photometric variability generally associated with heterogeneous, cloud-covered atmospheres. The spectral character of these variations yields insight into the particle sizes and vertical structure of the clouds. Here we present the results of a high precision, ground-based, near-infrared, spectral monitoring study of two mid-type L dwarfs that have variability reported in the literature, 2MASS J08354256−0819237 and 2MASS J18212815+1414010, using the SpeX instr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…It is important to note, however, that these studies do not consider the kinetics of cloud formation, and thus how cloud opacity varies with gravity on directly imaged exoplanets is still uncertain. Furthermore, interpreting spectra of the reddest objects still requires the inclusion of high altitude submicron aerosols and/or highly vertically extended cloud layers (Allart et al., 2020; Burningham et al., 2017; Hiranaka et al., 2016; Kellogg et al., 2017; Lew et al., 2016; Manjavacas et al., 2018; Schlawin et al., 2017; Stone et al., 2020).…”
Section: Insights From Theorymentioning
confidence: 99%
“…It is important to note, however, that these studies do not consider the kinetics of cloud formation, and thus how cloud opacity varies with gravity on directly imaged exoplanets is still uncertain. Furthermore, interpreting spectra of the reddest objects still requires the inclusion of high altitude submicron aerosols and/or highly vertically extended cloud layers (Allart et al., 2020; Burningham et al., 2017; Hiranaka et al., 2016; Kellogg et al., 2017; Lew et al., 2016; Manjavacas et al., 2018; Schlawin et al., 2017; Stone et al., 2020).…”
Section: Insights From Theorymentioning
confidence: 99%
“…From the astrophysical perspective, we can qualitatively evaluate the likelihood for HD106906b, an early L-type planetary-mass companion to be rotationally modulated only in the F127M band but not in the other two bands. Multiwavelength and time-resolved observations of ultra-cool dwarfs have found that the rotational modulations for the majority brown dwarfs and planetary-mass companions are wavelength-dependent and have higher amplitudes at shorter wavelengths than longer wavelengths (e.g., Apai et al 2013;Yang et al 2015;Zhou et al 2016;Schlawin et al 2017;Zhou et al 2019). These findings are consistent with a model prediction based on Mie-scattering calculation (Hiranaka et al 2016;Lew et al 2016;Schlawin et al 2017).…”
Section: Rotational Modulations Of Hd106906bmentioning
confidence: 99%
“…Multiple studies have used time-resolved ground-based photometry (e.g., Artigau et al 2009;Radigan et al 2012;Biller et al 2013;Radigan 2014), spectroscopy (e.g., Schlawin et al 2017), or space-based spectrophotometry (e.g., Buenzli et al 2012Buenzli et al , 2015Yang et al 2015Yang et al , 2016Karalidi et al 2016;Lew et al 2016) to explore the variations of the near-infrared (near-IR) colors of rotating brown dwarfs (from mid-L to T8 spectral types). All of these studies found gray, i.e., only weakly wavelength-dependent modulations in the near-IR, even for objects with large-amplitude (>10%) modulations.…”
Section: Introductionmentioning
confidence: 99%